Pelaksanaan Transparansi Perjanjian Kerja Terhadap Pekerja PKWT Di Perusahaan Cabang ID Express Jimbaran - Prince Gidion Simanjuntak; I Made Sarjana (Jurnal Hukum dan Sosial Politik, 2023)
The purpose of this study was to find out the implementation of the Specific Time Work Agreement (PKWT) and the factors causing the implementation of the Specific Time Work Agreement (PKWT) without transparency in the provision of work agreements to workers at ID Express Jimbaran. The normative research method was used in this research with a statutory approach, a historical approach to compare with a conceptual approach. This study also uses legal materials such as primary, secondary, and tertiary legal materials. The results of this study indicate that the procedure for implementing a Specific Time Work Agreement (PKWT) carried out by ID Express Jimbaran is not in accordance with Article 59 paragraph (1) and paragraph (3) of Law no. 13 of 2003 concerning Manpower. Internal factors causing the lack of transparency in the implementation of the Specific Time Work Agreement (PKWT) at ID Express Jimbaran are the quality and behavior of human resources, organizational culture, and management policies and practices. Meanwhile, the external factors causing the absence of transparency in the implementation of the Specific Time Work Agreement (PKWT) at ID Express Jimbaran are government and customer policies.